2018
DOI: 10.3389/fpls.2018.01326
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Water Deficit Limits Maize Kernel Setting in Association With Changes in the Source-Flow-Sink Relationship

Abstract: The kernel setting of maize varies greatly because of the timing and intensity of water deficits. This variation can limit leaf productivity (source), the translocation of assimilated sugars (flow), and yield formation (sink). To explain the decline in kernel setting of maize under water deficits from the perspective of source-flow-sink, a 3-year experiment was conducted under a rain shelter. Five water regimes were studied. One regime included well-irrigated (CK) treatment. Four regimes involved water deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 67 publications
4
41
0
Order By: Relevance
“…Many investigators found the growth and productivity of maize were increased by the application of adequate water irrigation every 10 days (Gomaa et al, 2014;El-Sobky & Desoky, 2017;Abo El-Ezz & Haffez, 2019) or 12 days (Yasin, 2016), 14 days (Solieman et al, 2019) and 15 days (Gomaa et al, 2015) as compared with prolonging irrigation intervals more than those periods. On the other hand, exposing maize plants to water stress condition by skipping one or more irrigations caused a depression in the yield and its components of maize as reported by Ashraf et al (2016), El-Sobky & El-Naggar (2017), Mohammed et al (2017) and Li et al (2018). Under the minimum water conditions, the best option for maize production, yield improvement and yield stability is growing varieties are more tolerant for drought stress (Gabr et al, 2018;Hategekimana et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Many investigators found the growth and productivity of maize were increased by the application of adequate water irrigation every 10 days (Gomaa et al, 2014;El-Sobky & Desoky, 2017;Abo El-Ezz & Haffez, 2019) or 12 days (Yasin, 2016), 14 days (Solieman et al, 2019) and 15 days (Gomaa et al, 2015) as compared with prolonging irrigation intervals more than those periods. On the other hand, exposing maize plants to water stress condition by skipping one or more irrigations caused a depression in the yield and its components of maize as reported by Ashraf et al (2016), El-Sobky & El-Naggar (2017), Mohammed et al (2017) and Li et al (2018). Under the minimum water conditions, the best option for maize production, yield improvement and yield stability is growing varieties are more tolerant for drought stress (Gabr et al, 2018;Hategekimana et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…In our study, under rainfed conditions, the number of kernels decreased by 17.7% in 2017 and 21.1% in 2018, compared with RI. Other studies observed a significant decrease in number of kernels by 31.13% [27], and 19% [28] under drought stress during flowering period. Maize crops were found to be particularly susceptible to drought at the flowering stage [29].…”
Section: Discussionmentioning
confidence: 86%
“…Gurney et al (2002) found that a tolerant maize cultivar that produced high grain yield in the presence of Striga asiatica infection maintained higher rates of photosynthesis in the field in comparison to a susceptible cultivar. As drought stress reduces leaf area, accelerates leaf senescence, decreases leaf source activity, and changes numerous physiological and biochemical processes (Zaidi et al, 2004;Wahid et al, 2005;Li et al, 2018), the retention of green leaf area in the DTSTR hybrids under parasite infection may promote high rates of photosynthesis leading to increased kernel setting and grain yield under drought stress (Li et al, 2018;Tani et al, 2019). At the same time, the emphasis on enhanced vegetative growth, less visible leaf senescence, and synchronized male-female flowering of lines during the second stage of selection under managed drought stress may further accentuate photosynthetic activity to boost performance of the DTSTR hybrids under both drought stress and Striga infestation.…”
Section: Discussionmentioning
confidence: 99%